Avaliação da sustentabilidade de sistemas de produção da cana-de-açúcar no estado de São Paulo: uma proposta metodológica e de modelo conceitual - Cardoso, Bruno Oliveira (2013)
The sugar cane culture is one of the most ancient ones in Brazil. Nowadays, the cultivation of cane is the third most important in the country, mainly for representing an alternative and renewable source of energy. Environment and social equity concern have gotten stronger in the last years, especially due to market globalization. As a consequence of society s awareness, roused by this new attitude in the world, comes the need to adapt agriculture and agro industrial activities in order for all production systems to generate positive impacts to the environment and society. Therefore, sustainability has become the number one competition factor to the agricultural chains. A methodology entitled Sustain Sugar Method was developed in this research for the evaluation of sustainability in environmental, economical and social dimensions of the sugar cane production in the state of São Paulo. This methodology was made with adequate sustainability indicators to the case. A conceptual model of this system was developed in the state of São Paulo; it follows criteria and has attributes which represent the complexity of the theme sustainability. It can also effectively guide the gathering and validation of the sustainability indicators and its thresholds so that it is an effective tool to the responsible decisive organs and formulators of public policies. The methodology used for the model formulation as well as for the construction of the methodological proposal was: i) gathering of available information about sustainable sugar cane production; ii) formulation of indicators from specialized literature; e iii) the proposed indicators were systemized and organized in the Sustain Sugar Database and later validated by consulting specialists of the academic and production fields, plants and producers through remote consults (Applying the Delphi consult Technique to the specialists) and through a workshop. With this model and the method, the objective is to outline the sustainable sugar cane productive system in the state of São Paulo.